Effect of Cd and S sources on the morphologies of CdS synthesized by solvothermal reactions in mixed solvents - Anukorn Phuruangrat (2018)
CdS (hcp) was solvothermally synthesized from different Cd and S sources (Cd(NO3)2, CdCl2, Cd(CH3COO)2, (NH4)2S, CH3CSNH2, NH2CSNH2and CH5N3S) at 200 °C in mixed solvents of ethylenediamine and butylamine. The phase was detected using X-ray diffraction (XRD) and selected area electron diffraction (SAED). The SAED pattern is in accordance with that of the simulation. Scanning and transmission electron microscopies (SEM and TEM) revealed the presence of different products consisting of nano-wires, nano-rods and tetra-pods controlled by Cd and S sources. High resolution TEM (HRTEM) showed that the products grew in [0 0 1] direction that was both parallel with and normal to their (1 0 0) and (0 0 2) planes, respectively. Raman spectra showed the same fundamental and overtone modes at 300 and 600 cm-1, respectively. © 2009 Elsevier B.V. All rights reserved.